Panuveitis after covishield vaccination in an undiagnosed immunocompromised patient: A rare case report from Nepal (Journal of Kathmandu Medical College, 2022)
With the emergence of vaccines for the novel coronavirus, a new ray of hope came into human society. Yet the adverse effects of vaccination on some candidates without allergic tests might cause a detrimental change in the future. An interesting case of panuveitis in a 34-year-old male after the ChAdOx1 nCoV19 (covishield) vaccination is reported here. The respective management of the patient was done after comprehensive ocular and systemic evaluation. It is understood that vaccination is vital in controlling this pandemic, but the immunologic response due to this novel vaccine is also a concern.